The attention to young former imprisoned people of 18-21 years - Oscar Norbert Raymond-Correa (Universidad de Guantánamo, 2012)
This Investigation was accomplished in the circumscription 193 of the Popular Council number 4 in the Northern community El Caribe where we noticed that the attention to young, formerly imprisoned people, (18-21 years old) from the perspective of physical recreational activities is low, which is why we set about to increasing the power of this aspect. The objective pursued in the paper is to create a system of physical recreational activities to increase the interest of young former imprisoned people. The scientific methods used in the development of this investigation are those of the theoretical, empiricist and mathematician levels, they allowed accomplishing a diagnosis of the present-day situation of the object of investigation; the obtained results prove the feasibility of the proposal, designed to be introduced in social practice, and verified through the method: consultation with experts. What's innovative about this investigation is that the circumscription 193 of the Popular Council number 4 in the Northern community El Caribe makes good use of the potentialities of the physical recreational activities to increase the power of the attention and interest of young formerly imprisoned people of 18 to 21 years old.